Occupational choice and self-employment: Are they related? - Alina Sorgner; Michael Fritsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Often, a person will become an entrepreneur only after a period of dependent employment, suggesting that occupational choices precede entrepreneurial choices. We investigate the relationship between occupational choice and self-employment. The findings suggest that the occupational choice of future entrepreneurs at the time of labor market entry is partly guided by a taste for skill variety, the prospect of high earnings, and occupational earnings risk. Entrepreneurial intentions may also emerge after gaining work experience in a chosen occupation. We find that occupations characterized by high levels of unemployment and earnings risk, relatively many job opportunities, and high self-employment rates foster the founding of an own business. Also, people who fail to achieve an occupation-specific income have a tendency for selfemployment.
Keywords: L26; J24; D01; 330; entrepreneurial choice; occupation-specific determinants of entrepreneurship; risk preferences; taste for variety